Surface enhanced dynamic nuclear polarization solid-state NMR spectroscopy sheds light on Brønsted-Lewis acid synergy during the zeolite catalyzed methanol-to-hydrocarbon process - Dutta Chowdhury, Abhishek; Yarulina, Irina; Abou-Hamad, Edy; Gurinov, Andrei; Gascon, Jorge (Chemical science (Cambridge), 2019)
After a prolonged effort over two decades, the reaction mechanism of the zeolite-catalyzed methanol-to-hydrocarbon (MTH) process is now well-understood: the so-called 'direct mechanism' ( via direct coupling of two methanol molecules) is responsible for the formation of the initial carbon-carbon bonds, while the hydrocarbon pool (HCP)-based dual cycle mechanism is responsible for the formation of reaction products. While most of the reaction events occur at zeolite Brønsted acid sites, the addition of Lewis acid sites ( i.e. , via the introduction of alkaline earth cations like calcium) has been shown to inhibit the formation of deactivating coke species and hence increase the catalyst lifetime. With the aim to have an in-depth mechanistic understanding, herein, we employ magic angle spinning surface-enhanced dynamic nuclear polarization solid-state NMR spectroscopy to illustrate that the inclusion of Lewis acidity prevents the formation of carbene/ylide species on the zeolite, directly affecting the equilibrium between arene and olefin cycles of the HCP mechanism and hence regulating the ultimate product selectivity and catalyst lifetime. Surface-enhanced dynamic nuclear polarization solid-state NMR spectroscopy has been applied to identify the role of surface-carbene species and elucidating Brønsted-Lewis acid synergy during the zeolite-catalyzed methanol-to-hydrocarbon process.